PENGARUH MODEL PROJECT BASED LEARNING (PjBL) BERBASIS SCIENTIFIC APPROACH TERHADAP KETERAMPILAN BERPIKIR KREATIF SISWA KELAS X SMAN 7 BONE - Nurhua; Ali, Muhammad; Adiansyah, Romi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The PjBL learning model is a learning that uses projects as the core of learning, by using PjBL it is proven to increase student creativity by using PjBL it is expected that students are able to trigger active thinking skills, can work together and carry out learning creatively. PjBL is a learning model that uses projects as a learning process to achieve knowledge, skills, and attitude competencies. The research used is quantitative research with the type of Pre-Experimental Design research with the type of One Group Pre-Test and Post-Test Design. The population consists of 5 classes and sampling is done using purposive sampling technique. The research sample is class X E. 3 SMAN 7 SMAN 7 BONE with a total of 27 students. The data collection technique used in this study is the provision of Pre and Post test sheets of student concept understanding, and documentation. Based on the results of the research that has been done it can be concluded, the Project Based Learning (PjBL) Model based on the Scientific Approach is proven to improve the creative thinking skills of class X students of SMAN 7 Bone. This is shown by an increase in the average pre-test score of 63.52 to 84.81 on the post-test. Every indicator of creative thinking, especially elaboration, experienced significant improvement. Statistical tests showed a significant result (p = 0.000), indicating a positive effect of the PjBL model. This learning model also creates an active, contextual learning environment and encourages optimal development of 21st-century skills.